PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP FINANCIAL PERFORMANCE DENGAN SUPPLY CHAIN INTEGRATION DAN ORGANIZATIONAL LEARNING SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PUBLIK SEKTOR MANUFAKUR DI SURABAYA DAN SIDOARJO - Adrian - Kurniawan; Devie Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the affect of transformational leadership to financial performance by using supply chain integration and organizational learning as intervening variables on manufacturing firms in Surabaya and Sidoarjo. The sample used in this study was manufacturing firms in Surabaya and Sidoarjo listed on Bursa Efek Indonesia (BEI) which generate profit in the last 5 years. Partial Least Square method used to analyze the data of 300 respondents from 30 manufacturing firms in Surabaya and Sidoarjo. The result of this study showed that transformational leadership had positive and significant affect on supply chain integration and organizational learning, organizational learning had positive and significant affect on financial erformance, and transforamtional leadership and supply chain integration had positive affect on financial performance, but not significant